A Review of Live Survey Application: SurveyMonkey and SurveyGizmo - Maisaarah Abd Halim; Cik Feresa Mohd Foozy; Isredza Rahmi; Aida Mustapha (JOIV : International Journal on Informatics Visualization, 2018)
Live survey application is being used to get opinion from others. There are several types of live survey monkey that currently popular such as SurveyMonkey and Survey Gizmo. These live survey application will be compared in several types of features to identify which is suitable for education purpose. The comparison will be on the advantage and disadvantage of both applications, the security issues and solution on how to solve the issues. Three (3) phases involve in the research methodology such as searching, identify and the result of the comparison. The output of this paper is a comparison table that can be used for educational purpose.